THE ROLES OF TALENT DEVELOPMENT INSTITUTE IN DEVELOPING AN ORGANIZATION’S EMPLOYEE SOFT SKILLS - Santosa, Sonny; Anggraeni, Tri; Elizabeth, Elizabeth; Novianti, Rini; Susanto, Susanto (Yayasan Education and Social Center, 2022)
This research aims to become one of management’s references to maximize the HR’s functions, especially those related to talent development. Human Resource is expected to optimize the planning on itself. This includes on how to recruit the right people for the company as well as on how to develop and to utilize human existing resources to support the business growth. This research is a case study and a project plan of Talent Development at PT. Indako Group – Medan. The issues raised in this research are what causes HRD considered not develop employee soft-skills maximally and how much HRD plays a role and functions in developing employee soft-skills. This research belongs to qualitative research with literature study in collecting the data. The discussion found out that HRD’s day-to-day activities were limited only to administrative activities. Whereas HRD should play a major role in developing the employee soft skills. Regarding the talent development issue, the researchers suggest determining back the organizational culture and mapping the competence professionally. Thus, the employees can implement the leadership values in themselves, named Build Superior Talent. Still, they can transform the leadership values determined so that talent can be created. Next, HRD is expected to implement core values such as Competence, Opening Mind, Care, Knowledge, Passion, Integrity, Teamwork. All of these are called COCKPIT and complete the process of employee soft-skill development